Infectious disease hotlines to provide advice to general practitioners: a prospective study - Anna Luce Sette; Patrice François; Philippe Lesprit; Virginie Vitrat; Olivier Rogeaux; Emma Breugnon; Marion Baldeyrou; Véronique Mondain; Bertrand Issartel; Solen Kerneis; Sylvain Diamantis; Delphine Poitrenaud; et al. (BMC, 2023)
Abstract Background Telephone hotlines in infectious diseases (ID) are part of antimicrobial stewardship programs designed to provide support and expertise in ID and to control antibiotic resistance. The aim of the study was to characterize the activity of the ID hotlines and estimate their usefulness for general practitioners (GPs). Methods This was a multicenter prospective observational study in different French regions. ID teams involved in antimicrobial stewardship with a hotline for GPs were asked to record their advice from April 2019 to June 2022. In these regions, all GPs were informed of the ID hotline's operating procedures. The main outcome was usage rate of the hotlines by GPs. Results Ten volunteer ID teams collected 4138 requests for advice from 2171 GPs. The proportion of GPs using the hotline varied pronouncedly by region, from 54% in the Isere department, to less than 1% in departments with the lowest usage. These differences were associated with the number of physicians in ID teams and with the age of the hotline. These results highlighted the value of working time as a means of ensuring the permanence of expertise. The main reasons for calling were: a diagnostic question (44%); choice of antibiotic (31%). The ID specialist provided advice on antibiotic therapy (43%) or a proposal for specialized consultation or hospitalization (11%). Conclusions ID hotlines could help to strengthen cooperation between primary care and hospital medicine. However, the deployment and perpetuation of this activity require reflection concerning its institutional and financial support.